Angiotensin II receptor agonist antibodies are associated with microvascular damage in lupus nephritis. (April 2020) - Mejia-Vilet, J M; López-Hernández, Y J; Santander-Vélez, J I; Trujeque-Matos, M; Cruz, C; Carranza de la Torre, C A; Espinosa-Cruz, V; Espinosa-González, R; Uribe-Uribe, N O; Morales-Buenrostro, L E
Angiotensin II type 1 receptor agonist antibodies (AT1R-AAs) have been associated with hypertension, atherosclerosis and vascular inflammation in human diseases. The aim of the study was to evaluate the prevalence of AT1R-AAs in active lupus nephritis (LN) patients and their association with vascular damage. One hundred and seven active LN patients underwent a complete clinical examination, measurement of AT1R-AAs, ambulatory blood pressure monitoring, carotid intima-media thickness measurement and morphometric analysis of subintimal fibrosis and medial hyperplasia of the vessels in the kidney tissue. Plasma AT1R-AAs were positive in 58 (54.2%) patients. The Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) score, complement C3 and C4 levels and titers of anti-dsDNA antibodies were higher in the group with positive AT1R-AAs compared with those with negative AT1R-AAs. The AT1R-AA titers correlated with anti-dsDNA antibody titers and with complement C3 and C4 serum levels. In the kidney biopsy, the percentage of subintimal fibrosis and the area of medial hyperplasia were greater in the AT1R-AA-positive patients. No differences in arterial pressure, carotid intima-media thickness and response to therapy were detected. In conclusion, AT1R-AAs are prevalent in active LN patients and are associated with histologic features of microvascular damage.